RESILIENCE OF DIVORCED MOTHERS IN HARJAMUKTI VILLAGE, CIREBON, INDONESIA - Meilani Dewi Setiamanah; Jumayar Marbun; Nurhayani Lubis (Indonesian Journal of Social Work, 2021)
This study is intended to find out how the resilience of divorced mothers in Harjamukti Village, Harjamukti District, Cirebon City, namely in the aspect of personal competence, believing in oneself, accepting positive change, self-control and aspects of spiritual influence. The research method is a quantitative descriptive survey with a sample of 50 mothers who are divorced, have family dependents and become the head of the family who live in Harjamukti Village, Harjamukti District, Cirebon City. The data collection techniques were questionnaires and documentation studies, with measuring instruments: the CD-RISC scale developed by Connor & Davidson, and previously modified. The results showed that the respondent's level of resilience was high with a score of 5,996. There are three aspects that are in the high category, namely: Personal Competence aspect (1.434), Accepting Change positively (1.412), and Spiritual Influence aspect (802). While the other two aspects are in the medium category, namely: the aspect of Self-Belief (1.643) and the aspect of Self-Control (704). Respondents who are resilient after divorce and can get out of stressful situations are able to carry out their dual roles, as housewives as well as heads of families. Respondents have all the components needed to shape them into a resilient person (although not all).